2018
DOI: 10.1212/wnl.0000000000006500
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal treatment trial of rituximab in progressive MS

Abstract: ObjectivesTo perform a phase 1b assessment of the safety and feasibility of intrathecally delivered rituximab as a treatment for progressive multiple sclerosis (PMS) and to evaluate the effect of treatment on disability and CSF biomarkers during a 1-year follow-up period.MethodsThree doses of rituximab (25 mg with a 1-week interval) were administered in 23 patients with PMS via a ventricular catheter inserted into the right frontal horn and connected to a subcutaneous Ommaya reservoir. Follow-ups were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 28 publications
0
31
0
1
Order By: Relevance
“…Die Datenlage bezüglich intrathekaler Applikation von CD20-depletierenden monoklonalen Antikörpern ist gering [87]. Ferner ist hervorzuheben, dass es bei RMS-Patienten unter Ocrelizumab im Vergleich zu Interferon-β1a zu mehr Varizella-Zoster-Infektionen (17 vs. 8 [25]) und bei PPMS-Patienten unter Ocrelizumab im Vergleich zu Placebo zu mehr oralen Herpesinfektionen (2,3 % vs. 0,4 %; [26]) gekommen ist.…”
Section: Schwangerschaften Unter Cd20gerichteter Therapieunclassified
“…Die Datenlage bezüglich intrathekaler Applikation von CD20-depletierenden monoklonalen Antikörpern ist gering [87]. Ferner ist hervorzuheben, dass es bei RMS-Patienten unter Ocrelizumab im Vergleich zu Interferon-β1a zu mehr Varizella-Zoster-Infektionen (17 vs. 8 [25]) und bei PPMS-Patienten unter Ocrelizumab im Vergleich zu Placebo zu mehr oralen Herpesinfektionen (2,3 % vs. 0,4 %; [26]) gekommen ist.…”
Section: Schwangerschaften Unter Cd20gerichteter Therapieunclassified
“…Participants were recruited at the neurology departments of Norrland's University Hospital, Umeå and Uppsala Hospital, Sweden between 27th June 2009 and 11th May 2015. Inclusion-and exclusion criteria are described in detail elsewhere [1]. Baseline characteristics for both studies are shown in Table 1.…”
Section: Study Cohortmentioning
confidence: 99%
“…In the original ITT-PMS study, participants received an Ommaya reservoir as an access point for intraventricular injections [1].…”
Section: Intrathecal (It) Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…Rituximab also showed efficacy in ameliorating demyelinating disorders of the CNS. 12 Intrathecal administration of RTX in progressive MS was well tolerated, 13 demonstrating good tolerability and efficacy in cases of both relapsing and progressive forms of MS. 14 The risk of John Cunningham (JC) virus and progressive multifocal leukoencephalopathy (PML) in MS patients was lowest in RTX-treated MS patients as compared to natalizumab, fingolimod or other diseasemodifying therapy (DMT). 15,16 In this work, we systematically investigated the effects of RTX on ameliorating EAE disorder.…”
Section: Introductionmentioning
confidence: 99%